2017
DOI: 10.1080/17436753.2017.1366733
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterisation of KNNS–BNKZ lead-free piezoceramics

Abstract: Promising piezoelectric properties have been reported recently for lead-free 0.96(K0.48Na0.52Nb0.95Sb0.05)-0.04Bi0.5(Na0.82K0.18)0.5ZrO3 (KNNS-BNKZ) ceramics. The presence of coexisting ferroelectric rhombohedral and tetragonal phases is thought to play a key role in their functional properties, but a thorough understanding is currently lacking. In this experiment, (1-x)KNNS-(x)BNKZ ceramics with x = 0 to 0.05 were prepared by the mixed-oxide method. High resolution synchrotron x-ray powder diffraction (SXPD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…Thermal evolution of (a),(b) lattice parameters and (c),(d) phase fractions of rhombohedral (R), orthorhombic (O) and tetragonal (T) phases for 0BNKZ and 1BNKZ compositions showing the widening of the phase transition range. Note that the uncertainties in lattice parameters and phase fractions are typically less than 0.002% and 1%, respectively.Although the identification of phase formation at room temperature described in previous work indicated the occurrence of O-T coexisting phases in the 1BNKZ composition[31], the contour plots of the thermally-induced SXPD profiles(Figure 4) in the present results revealed contradictory results. The coexistence of R-O was observed clearly in the temperature range of -73C to -43C, whereas the O-T mixed phase occurred for temperatures between 87C and 117C, as seen in the figure.…”
contrasting
confidence: 78%
See 2 more Smart Citations
“…Thermal evolution of (a),(b) lattice parameters and (c),(d) phase fractions of rhombohedral (R), orthorhombic (O) and tetragonal (T) phases for 0BNKZ and 1BNKZ compositions showing the widening of the phase transition range. Note that the uncertainties in lattice parameters and phase fractions are typically less than 0.002% and 1%, respectively.Although the identification of phase formation at room temperature described in previous work indicated the occurrence of O-T coexisting phases in the 1BNKZ composition[31], the contour plots of the thermally-induced SXPD profiles(Figure 4) in the present results revealed contradictory results. The coexistence of R-O was observed clearly in the temperature range of -73C to -43C, whereas the O-T mixed phase occurred for temperatures between 87C and 117C, as seen in the figure.…”
contrasting
confidence: 78%
“…For tan, the highest loss values near room temperature were found for the 0BNKZ composition because of its low relative density (<90%) as described previously. [31] A comparison of the contour maps of the {200} p XRD peak profiles, dielectric permittivity and loss tangent in the temperature range from 50C to 200C for 0BNKZ and 4BNKZ is presented in Figure 10(a) and (b) respectively, in order to study the relationship between the O-T structural phase transformation and dielectric properties. It was found that the abrupt change of dielectric permittivity for 0BNKZ starts at 100C and reached a peak at 125C, while the crystal structure fully transforms to tetragonal beyond 125C.…”
Section: Temperature-dependent Dielectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many various lead-free ceramic systems with perovskite structure have been success-fully studied [1] [2] [3] [4] [5], among which (Na,K)NbO 3 (KNN) based ceramics have attracted a lot of attention due to their strong ferroelectricity, high Curie temperature (about 420˚C). With compositional modification by combining KNN with other perovskite compounds to form KNN-based new solid solutions, such as KNNL [6] [7], KNNLS [8], KNNLST [9], KNNS-BNKZ [10], KNNS-BKZZ [11], the piezoelectric properties of ceramics are further enhanced (d 33 > 400 pC/N) [12] [13] [14], thereby it has become one of the most promising candidates for replacing Pb-based ceramics in the piezoelectric field. However, most of these studies focused on electrical properties, while the optical properties of the material are rarely mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the alkaline niobate-based lead free piezoelectrics have attracted considerable attention to replace lead-containing ceramics. Among them, potassium sodium niobate [(K,Na)NbO 3 , abbreviated as KNN] is considered as one of the best promising candidates to replace PZT [4][5][6]. Nevertheless, the piezoelectric activity of KNNbased ceramics is still inferior to that of most PZT materials because the alkaline elements of KNN are highly volatile at high temperature required for the synthesis of KNN [7].…”
Section: Introductionmentioning
confidence: 99%